2011
DOI: 10.1261/rna.030486.111
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of activation and repression by the alternative splicing factors RBFOX1/2

Abstract: RBFOX1 and RBFOX2 are alternative splicing factors that are predominantly expressed in the brain and skeletal muscle. They specifically bind the RNA element UGCAUG, and regulate alternative splicing positively or negatively in a position-dependent manner. The molecular basis for the position dependence of these and other splicing factors on alternative splicing of their targets is not known. We explored the mechanisms of RBFOX splicing activation and repression using an MS2-tethering assay. We found that the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 46 publications
11
81
0
Order By: Relevance
“…RBFOX proteins have a single RRM, highly homologous among the three paralogs, and their binding sites are exceptionally highly conserved in sequence (UGCAUG) and position across vertebrate evolution (Sun et al 2012). Mutations or deletions in RBFOX1 and RBFOX3 are found in epilepsy patients (Bhalla et al 2004;Lal et al 2013a,b), whereas copy-number variations in RBFOX1 are associated with autism spectrum disorders and spinocerebellar ataxias (Bill et al 2013;Weyn-Vanhentenryck et al 2014).…”
Section: Rbfox2-rna Binding Protein Fox-2 Homologmentioning
confidence: 99%
“…RBFOX proteins have a single RRM, highly homologous among the three paralogs, and their binding sites are exceptionally highly conserved in sequence (UGCAUG) and position across vertebrate evolution (Sun et al 2012). Mutations or deletions in RBFOX1 and RBFOX3 are found in epilepsy patients (Bhalla et al 2004;Lal et al 2013a,b), whereas copy-number variations in RBFOX1 are associated with autism spectrum disorders and spinocerebellar ataxias (Bill et al 2013;Weyn-Vanhentenryck et al 2014).…”
Section: Rbfox2-rna Binding Protein Fox-2 Homologmentioning
confidence: 99%
“…Interestingly, more recent work has shown cooperativity between MBNL and RBFOX proteins in iPSC reprogramming and muscle differentiation as well as in a myotonic dystrophy model (Venables et al 2013;Klinck et al 2014). RBFOX proteins have also been shown to regulate splicing in cooperation with other individual RBPs such as ESRP (Dittmar et al 2012), PTBP , and HNRNPH1 (Sun et al 2011). In particular, recent work has demonstrated that RBFOX proteins in mammals often function through the activity of a large multiprotein assembly that influences the binding and activity of RBFOX (LASR) ).…”
Section: Cooperation and Competition With Other Rbps Is A Common Featmentioning
confidence: 99%
“…Strikingly, the set of ERG interactors identified in our Y2H screen also included RNA-binding Fox-1 (RBFOX1 or A2BP1) and RNA-binding protein with multiple splicing (RBPMS or Hermes), two RBPs with canonical RNA-recognition motifs 34,35 (Supplementary Table 1). Whereas RBFOX proteins are wellcharacterized splicing factors, the role of RBPMS in mRNA processing remains unclear 36,37 . From these findings, we hypothesized that ERG might be recruited to specific mRNAs through its interaction with RBPs including RBPMS.…”
Section: Erg Is Recruited To Mrna Via Its Interaction With Rbpsmentioning
confidence: 99%